INTERNALISASI NILAI-NILAI AJARAN ISLAM MELALUI PROGRAM ECO-PESANTREN DALAM PELESTARIAN LINGKUNGAN HIDUP DI PONDOK PESANTREN (STUDI KASUS PONDOK PESANTREN JAUHARUL MAKNUN LASEM DUKUN GRESIK) - Muhammad Muhyiddin Mubarok; Muhammad Najib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the internalization of Islamic values through the eco-pesantren program in environmental conservation at Jauharul Maknun Islamic Boarding School, Lasem Dukun Gresik. This research employs a qualitative approach with a case study design. Data collection techniques include observation, in-depth interviews, and documentation. Data analysis uses the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The results show that the eco-pesantren program is implemented through waste management, environmental greening, routine cleanliness activities, and waste utilization. The internalization process of Islamic values is carried out through role modeling, habituation, teaching, direct practice, and reinforcement through rules and pesantren culture. This program has a positive impact on students' behavior, including increased religious awareness, the formation of clean and healthy living habits, and greater environmental concern. Therefore, the eco-pesantren program is proven to be effective as a medium for internalizing Islamic values in environmental conservation and in shaping students’ ecological character.